Կիլիկյան Հայաստանի քաղաքական զարթոնքի ազդակները (12-13-րդ դդ.) - Բոզոյան, Ազատ («Զանգակ - 97»)
The XII Century has a particular importance for the history of Armenian State system. It is characterized by the extension of the territories populated with Armeniens, by the creation of new Armenian poütical and cultural centers outside the Great Armenia, by the appearance of new political unites in Cilicia, which took the leaders role all overate Armenian oecumene. It is an impoitant period, when irreversible changes take place in the inferior and the exterior life of Armenia, in the national consciousness,in the structure of political and ecclesiastical oiganizaüons. Armenian localiües, as we!l as unique Spiritual and cultural centers, sprung up in а new geographical milieu (North Syria, Cilicia, Egypt, Palestine, Balkan Peninsula). These changes resulted in bringing the main military forces out of the polidcal centers of Armenia, which, in its tum, was the result of the occupation, by the Byzantine Empire, of Great Armenia's territories, as well as the fall of Bagratides' Kingdom.
Keywords: Հայոց պատմություն